Emotional branding and logo design: exploratory study in the Information Technology market - Coelho, Pedro Miguel dos Santos (2015)
The technical quality of products no longer guarantees a sustainable differentiation to technology manufacturers. The widespread use of best production practices and the easy access to low cost resources make it difficult for these manufacturers to offer unique products to their customers. A manufacturer can only maintain an innovative product in the market for short periods of time before a competitor can offer a similar product. Manufacturers struggle to differentiate themselves from competition in a market where products have been commoditized. They now seek this differentiation in the field of intangible assets, for instance investing in emotional branding to acquire and retain customers. Some of them integrate the brand signs in this approach, using the logo to trigger an affective response on customers, which contributes to develop an emotional relationship with the brand. This logic applies not only to consumers but also to customers on business-to-business markets. Analyzing customer responses to brands and logos, through a questionnaire, this Thesis addresses the tenuous differentiation between technological brands. It proposes that these brands should develop their associations related with benefits provided to customers, instead of focusing on product-centric associations. It also explores how logo design can elicit favorable reactions. It highlights that a slightly updated logo, with the inclusion of figurative elements, can achieve a stronger preference from customers, reinforcing the emotional bond between them and the brand. This Thesis ends suggesting that emotional branding and logo design, when integrated in a company-wide brand strategy, have the potential to become differentiating factors.